FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA - Ratih Astari, Anak Agung Mas; Suryanawa, I Ketut (E-Jurnal Akuntansi, 2017)
This study aims to analyze factors that influence earnings management. This research was conducted at Indonesian Stock Exchange. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2015. The method of determining the sample of this research is purposive sampling method in accordance with predetermined criteria and obtained a sample of 51 companies with a 4-year observation period so that the number of samples 204. The analysis technique used is multiple linear regression. Based on the results of the study showed that managerial ownership and institutional ownership has a significant negative effect on earnings management, this means increasing managerial ownership and institutional ownership then the decrease actions earnings management, firm size, leverage, profitability and sales growth positive and significant impact on the earnings management, this means that the higher the firm's size, leverage, profitability and sales growth then increasing earnings management action.
Keywords: Earnings Management, Managerial Ownership, Institutional Ownership, FirmSize, Leverage, Profitability, Sales Growth